2007
DOI: 10.1063/1.2431313
|View full text |Cite
|
Sign up to set email alerts
|

The NASA Spitzer Space Telescope

Abstract: The National Aeronautics and Space Administration's Spitzer Space Telescope (formerly the Space Infrared Telescope Facility) is the fourth and final facility in the Great Observatories Program, joining Hubble Space Telescope (1990), the Compton Gamma-Ray Observatory (1991-2000), and the Chandra X-Ray Observatory (1999). Spitzer, with a sensitivity that is almost three orders of magnitude greater than that of any previous ground-based and space-based infrared observatory, is expected to revolutionize our unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 60 publications
1
117
0
Order By: Relevance
“…We find that usingβ as an additional constraint for the 4.5 μm observations does not significantly improve the accuracy of our results. This is not surprising since the IRAC 4.5 μm channel is closer to the Spitzer diffraction limit of 5.5 μm (Gehrz et al 2007). We also find thatβ does not vary with stellar centroid position in the 5.8 and 8.0 μm observations, which are longward of the Spitzer of the diffraction limit.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We find that usingβ as an additional constraint for the 4.5 μm observations does not significantly improve the accuracy of our results. This is not surprising since the IRAC 4.5 μm channel is closer to the Spitzer diffraction limit of 5.5 μm (Gehrz et al 2007). We also find thatβ does not vary with stellar centroid position in the 5.8 and 8.0 μm observations, which are longward of the Spitzer of the diffraction limit.…”
Section: Discussionmentioning
confidence: 95%
“…Both the 3.6 and 4.5 μm channels of the IRAC instrument are shortward of the Spitzer 5.5 μm diffraction limit (Gehrz et al 2007) and exhibit undersampled PRFs whose shape changes as the stellar centroid moves from the center to the edge of a pixel causing intrapixel sensitivity variations. The PRFs in the 5.8 and 8.0 μm channels of the IRAC instrument exhibit a more Gaussian-like shape that is better sampled by the detector resulting in only small intrapixel sensitivity variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations are performed in the 3.6 μm and 4.5 μm bands of the InfraRed Array Camera (IRAC, Fazio et al 2004) on board the warm Spitzer Space Telescope (Werner et al 2004;Gehrz et al 2007). …”
Section: Mid-infrared Observations With Spitzermentioning
confidence: 99%
“…Recent near-infrared (NIR) and mid-infrared (MIR) surveys (e.g., 2MASS, Skrutskie et al (2006); DENIS, Epchtein et al (1994) and SAGE, Meixner et al (2006)) have revealed tens of thousands of AGB star candidates in Large Magellanic Cloud (LMC). The SAGE (Meixner et al 2006) survey has observed the LMC in the Spitzer Space Telescope (Spitzer; Gehrz et al 2007) Infrared Array Camera (IRAC; 3.6, 4.5, 5.8 and 8.0 μm) and Multiband Imaging Photometer for Spitzer (MIPS; 24, 70 and 160 μm) bands. Blum et al (2006) and Srinivasan et al (2009) (hereafter, Paper I) used SAGE photometry to identify about 7000 carbon-rich AGB star candidates in the LMC.…”
Section: Introductionmentioning
confidence: 99%